Comparison of novice and full-licenced driver common crash types in New South Wales, Australia, 2001–2011. (August 2015) - Mitchell, R.J.; Senserrick, T.; Bambach, M.R.; Mattos, G.
Highlights: Examination of crash and injury risk factors between novice and full-licenced drivers. Population-based linked police-reports and hospitalisation administrative data. Crash characteristics between novice and full-licence drivers were similar with most common crash types. Abstract: Objective: To examine the circumstances of passenger vehicle crashes for novice licenced drivers aged 17–25 years and to compare the crash circumstances of the most common crash types for novices to a sample of full-licence drivers aged 40–49 years. Method: A retrospective analysis was conducted of passenger vehicle crashes involving novice and full-licenced drivers during 1 January 2001 to 31 December 2011 in New South Wales (NSW), Australia. Results: There were 4113 injurious crashes of novice drivers. Almost half the novice driver crashes involved a single vehicle. Vehicle speed (33.2%), fatigue (15.6%) and alcohol (12.6%) were identified risk factors in novice driver crashes. Correspondence analysis for 4 common crash types for novice drivers revealed that the crash characteristics between novice and full-licenced drivers were similar. Conclusions: Similarities exist between novice driver and full-licenced driver crash risk for common crash types. Preventive strategies aimed at crash risk reduction for novice drivers may also benefit all drivers.